Effect of Aging on Change of Intention - Furstenberg, Ariel; Dewar, Callum D.; Sompolinsky, Haim; Knight, Robert T.; Deouell, Leon Y. (Frontiers in Human Neuroscience, 2019)
Decision making often requires making arbitrary choices (‘picking’) between alternatives that make no difference to the agent, that are equally desirable, or when the potential rewards are unknown. Using event-related potentials we tested the effect of age on this common type of decision making. We compared two age groups: ages 18-25, and ages 41-67 on a masked-priming paradigm while recording EEG and EMG. Participants pressed a right or left button following either an instructive arrow cue or a neutral free-choice picking cue, both preceded by a masked arrow or neutral prime. The prime affected the behavior on the Instructed and the Free-choice picking conditions both in the younger and older groups. Moreover, electrophysiological ‘Change of Intention’ was observed via Lateralized Readiness Potential (LRP) in both age groups – the polarity of the LRP indicated first preparation to move the primed hand and then preparation to move the other hand. However, the older participants were more conservative in responding to the instructive cue, exhibiting a speed-accuracy trade-off, with slower response times, less errors in incongruent trials, and reduced probability of EMG activity in the non-responding hand. Additionally, ‘Change of Intention’ was observed in both age groups in slow RT trials with a neutral prime as a result of an endogenous early intention to respond in a direction opposite the eventual instructing arrow cue. We conclude that the basic behavioral and electrophysiological signatures of implicit change of intention are common to a wide range of ages. However, older subjects, despite showing a similar dynamic decision trajectory as younger adults, are slower, more prudent and finalize the decision making process before letting the information affect the peripheral motor system. In contrast, the flow of information in younger subjects occurs in parallel to the decision process.